Homeschooling Implementation: Indonesian Parents' Experience During The COVID-19 Pandemic - nurussakinah daulay; wiwin hendriani; haerani nur; Sayidah Aulia 'ul Haque (STAI Hubbulwathan Duri, 2021)
This study aimed to explore parents' difficulties and efforts in implementing homeschooling during the Covid-19 pandemic from diverse regions in Indonesia. The research was conducted twice, namely three weeks after the enforcement of Large-Scale Social Restriction (PSBB) and ten months after that. The total participants involved were 385 parents in the first study and 105 parents in the second study in this exploratory study. The method used in this study was descriptive qualitative with the data collection using two open-ended questions online. The result showed that schools that had implemented online learning applications before the pandemic would make the parents, teachers, and students easier in facing homeschooling challenges. The school that never implemented online applications before the pandemic made the parents, teachers, and students notice overwhelmed by the challenges of homeschooling. Parents both actively and passively perform how to overcome homeschooling difficulties.